FORMULASI BLUSH ON STICK DENGAN ZAT PEWARNA ALAMI EKSTRAK KERING BUAH NAGA MERAH (HYLOCEREUS POLYRHIZUS L.) - Benni Iskandar; Meri Ernilawati; Ferdy Firmansyah; Neni Frimayanti (STIKES Cendekia Utama Kudus, 2021)
Blush On is a cosmetic preparation that applies color to the cheek with an artistic touch so that it it can enhance the aesthetics of Make up. One of the natural ingridients that can used as a dye is Red Dragon fruit (Hylocereus polyrhizus L.) because they contain the pigments betasianin that function as a color pigment. The Purpose of this study was to determine wheter the dry extract of red dragon fruit can be use as dye in blush on stick form and to evaluate the blush on form.The Blush on formula made using dyes from the dry extract of red dragon fruit with different concentration of 0%, 10%, 15% and 20% with additional ingridients of glycerin, zinc oxide, lanolin, isopropyl myristate, sodium metabisulfite, carnauba wax, talc and oleum rosae. The evaluation of product included organoleptic test, homogeneity test, pigment stability test, sotarge stability test, pH test, polish test, crack test, hedonic test and irritation test. All formulas have met the requirements of the homogeneity test, pH test, polish test and crack test. Organoleptic test showed the blush preparation has the specific odor of oleum rosae and the the blush has a solid stick. The blush with a concentration of 0% is white, the blush with a concentration of 10% is pink, the blush with a concentration of 15% is light purplish red, the blush with a concentration of 20% is dark purplish red. For F1 (10%), F2 (15%) and F3 (20%) preparations were only stable until week 5 and were unstable to light. The result of the irritation test showed that the blush preparation did not show any irritation reactions. The result of the hedonic test showed that F3 (20%) was the most preferred by the panelists